Livestock development policies in sub-Saharan Africa (2) - Hoste, Christian H. (Technical Centre for Agricultural and Rural Cooperation, 1999)
Two seminars, one focusing on West and Central Africa and the other on Eastern and Southern Africa, were organised to contribute to the debate on policies aimed at promoting effective and sustainable livestock development...